Agency Theory and Bounded Self-Interest - Bosse, Douglas A.; Phillips, Robert A. (Academy of Management Review, 2016)
Agency theory draws attention to certain behaviors of CEOs and boards that, in aggregate, create losses for society. The empirical literature, however, characterized by contentious findings, suggests that the current form of agency theory is not supporting a clear understanding of these behaviors and their costs. We propose a change to one assumption, with potentially profound implications. Expanding on the assumption of narrow self-interest underlying agency theory, we apply an empirically well-established refinement that self-interest is bounded by norms of reciprocity and fairness. The resulting logic is that perceptions of fairness mediate the relationships derived from standard agency theory through positively and negatively reciprocal behaviors. This mediating variable provides a parsimonious new way to help explain extreme results found in prior studies. Rather than aiming to limit CEOs’ self-serving behaviors, boards that apply these arguments improve social welfare by initiating positive reciprocity and avoiding unnecessary, welfare-reducing “revenge” behaviors.